Entrepreneurship Training and Mentoring for Sportswear Production at the Branch Leadership of LPM SMA Muhammadiyah Program Khusus Sambi Boyolali - Fatoni, Muhad; Susilo, Agus; Nur W, Anugrah; Sudarmanto, Eko; Septi Sistiasih, Vera; Nugroho, Hanif; Asy Syahidah, Annisa; Elka Fikri, Muhammad; Prihantara Utama, Bangun; Yaghfir Alifah, Fathimah; Safitri, Wanda (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The entrepreneurship training and mentoring initiative at PR IPM SMA Muhammadiyah PK Sambi Boyolali focuses on equipping members with essential skills in sportswear production and micro-business management. This program encompasses training in production techniques, business operations, and marketing strategies. The process is carefully structured, beginning with a thorough needs assessment, followed by a well-planned two-month program, and culminating in the development of educational materials aligned with a specialized Sports Entrepreneurship curriculum. Participants successfully produced themed sports jerseys and casual t-shirts, and also established a promising business unit within PR IPM SMA Muh. PK Sambi Boyolali. With its emphasis on sustainability, this initiative is poised to serve as a robust model for entrepreneurship development among students and other Muhammadiyah youth groups. Ongoing evaluations and adaptive program strategies are integral to ensuring the continued success and longevity of this endeavor.